Translation and validation of the cardiac rehabilitation barriers scale in the Czech Republic (CRBS-CZE): Protocol to determine the key barriers in East-Central Europe - Winnige, Petr; Batalik, Ladislav; Filakova, Katerina; Hnatiak, Jakub; Dosbaba, Filip; Grace, Sherry L (Medicine, 2020)
BACKGROUND: Cardiovascular diseases are highly prevalent and represent leading causes of morbidity worldwide, including in Central Europe. Cardiac rehabilitation (CR) is an effective method of secondary prevention, but utilization is low. Barriers to CR use in the Czech Republic are not well-characterized, and therefore we propose a protocol to translate and validate the cardiac rehabilitation barriers scale (CRBS). METHODS: In this multi-method study, we translated and cross-culturally validated the CRBS to Czech (CRBS-CZE) first through the following main steps: professional translation, reconciliation/harmonization, and cross-cultural adaptation, and piloting in 50 cardiac patients. A prospective study will be undertaken to psychometrically-validate the CRBS-CZE, where 300 to 600 cardiac inpatients eligible for phase II/outpatient CR will be recruited. Consenting participants will be informed about the CR program and their sociodemographic, clinical characteristics, and the CRBS-CZE administered. Factor analysis will be performed with oblique rotation, factors will be extracted based on eigenvalues, the examination of the scree plot, and factor loadings. The internal reliability of the total scale and subscales will be assessed with Cronbach alpha. Overall CRBS scores will be compared by patient characteristics such as sex, socioeconomic indicators, risk factor burden, and travel time to investigate content validity. Their CR enrollment, adherence (% of 24 prescribed sessions attended), and completion will be tracked. The second administration of CRBS-CZE will be undertaken in patients at 3 weeks after enrollment. To test criterion validity, t tests and Pearson correlation (for adherence) will be used to determine the association of these utilization indicators with CRBS scores. RESULTS: The translated version was considered by 2 bilingual CR experts. Some revisions and example additions were made to the items. Upon piloting with patients, some further edits were made. No additional barriers were raised. DISCUSSION: Through this study, a reliable and valid means of assessing patient's CR barriers will be established. Results will be used to identify ways to help patients overcome barriers to CR utilization.
Keywords: Psychometrics; Reproducibility of Results; psychometrie; reprodukovatelnost výsledků; Cardiac Rehabilitation; Česká republika; průzkumy a dotazníky; Prospective Studies; Czech Republic; překlady; Cardiovascular Diseases; Humans; kardiovaskulární rehabilitace; prospektivní studie; Translations; Surveys and Questionnaires; výzkumný projekt; Research Design; kardiovaskulární nemoci; lidé